Age and Gender Moderation in PLN Mobile Adoption: Roles of Effort, Social Influence, and Facilitation - Muhammad Shadiq Arifin; Raden Roro Yulianti Prihatiningrum; Laila Refiana Said; Siti Aliyati Albushairi (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study investigates the factors associated with actual PLN Mobile use among customers of PT PLN (Persero) in South and Central Kalimantan. The proposed model links effort expectancy and social influence to behavioral intention and links facilitating conditions and behavioral intention to use behavior while treating age and gender as moderators. An explanatory quantitative survey was administered to 330 active PLN Mobile users in South and Central Kalimantan. Respondents were selected purposively, and the model was estimated using Partial Least Squares Structural Equation Modeling in SmartPLS 4. Effort expectancy and social influence were significant antecedents of behavioral intention, whereas facilitating conditions and behavioral intention significantly predicted the use behavior. Age and gender significantly changed the strength of the paths from effort expectancy and social influence to intention and from facilitating conditions to the use behavior. The model accounted for 66.4% and 88.6% of the variance in behavioral intention and use behavior, respectively. Actual PLN Mobile use is jointly associated with perceived ease, interpersonal and institutional encouragement, enabling resources, user intention, and demographic variation. This study broadens the application of UTAUT by concurrently assessing age and gender as boundary conditions in a mobile application for an essential public utility. The evidence is based on cross-sectional, self-reported responses from users within the Kalimantan Selatan–Tengah (Kalselteng) service area.